Economics as a rhetorical language game - Raquel Mesquita Almeida (EconomiA, 2023)
Purpose: This paper aims to argue that Economics is not a neutral science. Design/methodology/approach: Post-structuralist perspective of Lyotard (1984), alongside the Pragmatics of Searle (1979) and Travis (1981) are useful for analyzing enunciations in mainstream Economics. Findings: Economists use illocutionary acts expressed in formal language to achieve perlocutionary effects. Because of the importance attached to objectivity in mainstream Economics, the use of artificial languages is preferred to natural language. However, formal language is preferred regarding its perlocutionary effects on economists' community. Originality/value: This paper puts together the Continental and the Analytical Philosophy and show, in an original manner, how their intersections and how they can be useful to better understand the epistemology of Economics.
Keywords: B41; B59; 330; Rhetorical economics; Philosophy of language; Mathematical formalism